Antimicrobial Susceptibility Patterns of Environmental Streptococci Recovered from Bovine Milk Samples in the Maritime Provinces of Canada - Cameron, Marguerite; Saab, Matthew; Heider, Luke; McClure, J Trenton; Rodriguez-Lecompte, Juan Carlos; Sanchez, Javier (Frontiers in Veterinary Science, 2016)
Determination of antimicrobial susceptibility of bovine mastitis pathogens is important for guiding antimicrobial treatment decisions and for the detection of emerging resistance. Environmental streptococci are ubiquitous in the farm environment and are a frequent cause of mastitis in dairy cows. The aim of the study was to determine patterns of antimicrobial susceptibility among species of environmental streptococci isolated from dairy cows in the Maritime Provinces of Canada. The collection consisted of 192 isolates identified in milk samples collected from 177 cows originating from 18 dairy herds. Results were aggregated into: 1) Streptococcus uberis (n = 70), 2) Streptococcus dysgalactiae (n = 28), 3) other Streptococci spp. (n = 35), 4), Lactococcus spp. (n = 32), and 5) Enterococcus spp. (n = 27). Minimum inhibitory concentrations (MIC) were determined using the Sensititre microdilution system and mastitis plate format. Multilevel logistic regression models were used to analyze the data, with antimicrobial susceptibility as the outcome. The proportion of susceptible Streptococcus uberis ranged from 23% (for penicillin) to 99% (for penicillin/novobiocin), with a median of 82%. All Streptococcus dysgalactiae were susceptible to all antimicrobials except for penicillin (93% susceptible) and tetracycline (18% susceptible). The range of susceptibility for other Streptococcus spp. was 43% (for tetracycline) to 100%, with a median percent susceptibility of 92%. Lactococcus spp. isolates displayed percent susceptibilities ranging from 0% (for penicillin) to 97% (for erythromycin), median 75%. For the antimicrobials tested, the MIC were higher for Enterococcus spp. than for the other species. According to the multilevel models, there was a significant interaction between antimicrobial and bacterial species, indicating that susceptibility against a particular antimicrobial varied among the species of environmental streptococci and vice versa. Generally, susceptibility decreased with increasing within-herd average somatic cell count, isolates recovered in mid-lactation were more susceptible that isolates recovered in early lactation, and isolates recovered in samples collected post-clinical mastitis were more susceptible than isolates recovered from non-clinical lactating quarters. The results of this research support continued susceptibility of environmental streptococci to beta-lactam antimicrobials. A departure from the expected susceptibility to beta-lactams was the apparent reduced susceptibility of Streptococcus uberis to penicillin.